Access to Justice and Labor Law Reform in Asia - Asri Wijayanti (Universitas Muhammadiyah Sidoarjo, 2016)
The existence of national labor law system guarantees fair is one of legal reform to achieve access to justice. This study aims to analyze whether the system of labor law has given capacity to achieve access to justice as the basis for implementing international labor relations in Asia. The method of this study is a normative legal research with statute approach. The findings support that there was an inconsistency on the substance of the legal structures that affect the low legal culture. The substance of the national labor law systems have not adapted the comprehensive International Labor Organization (ILO) conventions. Less robust system of national labor laws affect access to justice in the weak field of labor in the region.